TyG index and CBC-derived inflammatory indicators individual and mixed effects on all-cause and cardiovascular disease deaths in patients with CHD - Cai, Lipeng; Yan, Jiangrong; Sun, Lei; Dan, Weichao (Frontiers in Cardiovascular Medicine, 2025)
Background and aimsCurrently, most epidemiological investigations have concentrated on exploring the correlation between a singular indicator and the risk of cardiovascular disease. In clinical practice, a single indicator often fails to comprehensively represent a patient's health status. Consequently, it is crucial to thoroughly evaluate the influence of multiple indicators on disease prediction. Recently, the Triglyceride-Glucose Index (TyG Index) and inflammatory markers derived from CBC (CBC) have garnered increasing attention. Nevertheless, research on the individual and synergistic impacts of the TyG index and inflammatory indices on the risk of all-cause mortality and cardiovascular death in patients with coronary heart disease (CHD) remains scarce. To develop a more accurate risk assessment instrument for the clinic and to provide a novel strategy and framework for the management of individuals with coronary artery disease (CAD).Methods and resultsThis study identified patients with CHD aged 20 years and older from five cycles of National Health and Nutrition Examination Survey (NHANES) data spanning 2009 to 2018. We employed weighted logistic regression analysis and the restricted cubic spline (RCS) approach to investigate the TyG index and CBC-derived inflammatory indicators in relation to the risk of all-cause mortality and cardiovascular mortality in patients with CHD. The cumulative exposure effect of these measures was estimated utilizing a Weighted Quantitative Scoring (WQS) model. In the unadjusted model, ln(SII) (OR = 1.8, 95% CI = 1.05 ∼ 3.06, P = 0.032), ln(SIRI) (OR = 2.08, 95% CI = 1.45 ∼ 2.98, P < 0.001), ln(MLR) (OR = 2.53, 95% CI = 1.55 ∼ 4.13, P < 0.001), ln(NLR) (OR = 2.57, 95% CI = 1.44 ∼ 4.60, P = 0.002), and ln(PLR) (OR = 2.56, 95% CI = 1.53 ∼ 4.29, P < 0.001) exhibited a positive correlation with the risk of all-cause mortality. In the model, after comprehensive adjustment for confounders, it continued to exhibit a substantial association with the risk of mortality from CHD. RCS analysis revealed a nonlinear dose-response relationship between Monocyte-to-Lymphocyte Ratio (MLR), Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), Systemic Immune-Inflammation Index (SII), and Systemic Inflammation Response Index (SIRI) and the probability of all-cause mortality (P -nonlinear < 0.05). The WQS model indicated that simultaneous exposure to the TyG index and inflammatory markers derived from CBC was significantly and positively associated with the risk of all-cause mortality and cardiovascular death in patients with CAD (OR = 1.68, 95% CI = 1.22–2.30, P = 0.009, and OR = 2.2, 95% CI = 1.42–3.42, P = 0.0004), with the Neutrophil-to-Platelet Ratio (NPR) and SII being the most significant contributors to the overall risk.ConclusionOur investigation demonstrated that the TyG index and inflammatory indices generated from CBC are significant risk factors for all-cause mortality and cardiovascular mortality in patients with CHD, with NPR and SII representing the largest proportion of these factors.